2023
DOI: 10.26434/chemrxiv-2023-6kt1w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Difluoromethyl-1,3,4-oxadiazoles are selective, mechanism-based, and essentially irreversible inhibitors of histone deacetylase 6

Abstract: Histone deacetylase 6 (HDAC6) is an important drug target in oncology and non-oncological diseases. Most available HDAC6 inhibitors (HDAC6i) utilize a hydroxamic acid as zinc-binding group which limits the therapeutic opportunities due its genotoxic potential. Recently, difluoromethyl-1,3,4-oxadiazoles (DFMOs) were reported as potent and selective HDAC6i, but their mode of inhibition remained enigmatic. Herein, we report that DFMOs act as mechanism-based and essentially irreversible HDAC6i. Biochemical data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…15 The tight-binding properties of the active species were confirmed by jump-dilution and dialysis experiments. 15 Overall, there is now clear evidence that DFMOs act as mechanism-based, slow-and tight-binding HDAC6 inhibitors. 15 Also in 2023, Barinka and co-workers performed a systematic comparison of the DFMO Cmpd7 (Figure 2C) and its corresponding hydroxamic acid analog, thereby clearly supporting the observation that DFMOs are new ZBGs with unparalleled selectivity for HDAC6 over all other HDAC isoforms.…”
Section: Inhibitors and Degradersmentioning
confidence: 87%
See 3 more Smart Citations
“…15 The tight-binding properties of the active species were confirmed by jump-dilution and dialysis experiments. 15 Overall, there is now clear evidence that DFMOs act as mechanism-based, slow-and tight-binding HDAC6 inhibitors. 15 Also in 2023, Barinka and co-workers performed a systematic comparison of the DFMO Cmpd7 (Figure 2C) and its corresponding hydroxamic acid analog, thereby clearly supporting the observation that DFMOs are new ZBGs with unparalleled selectivity for HDAC6 over all other HDAC isoforms.…”
Section: Inhibitors and Degradersmentioning
confidence: 87%
“…17 Almost in parallel, based on crystallographic and mechanistic experiments, the Christianson and Hansen groups disclosed the full experimental details of their initial conference contribution, 24 confirming that the DFMO warhead undergoes an enzyme-catalyzed ring-opening reaction, resulting in a deprotonated difluoroacetylhydrazide as active species (Figure 3). 15 The strong anionic zinc coordination of the deprotonated difluoroacetylhydrazide and the binding of the difluoromethyl moiety in the P571 pocket of the CD2 of HDAC6 finally results in an essentially irreversible inhibition of the enzyme. 15 The tight-binding properties of the active species were confirmed by jump-dilution and dialysis experiments.…”
Section: Inhibitors and Degradersmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible ways to achieve HDAC6 degradation via the hydrophobic tagging approach could include the use of selective HDAC6 ZBGs with tight-binding properties and long residence times, such as 2-(difluoromethyl)-1,3,4oxadiazoles (DFMOs) in combination with the optimization of both the linker and the HyT. 26,27 Taken together, in this proof-of-concept study, we demonstrated for the first time that the hydrophobic tagging approach is suitable for the targeted degradation of HDAC1. Further optimization studies of the prototypical compounds reported in this work are underway.…”
mentioning
confidence: 99%